Economic and social conditioning factors for organizations in Latin America: Strategy and development (2019)
The main objective of this study is to present the main features that the environment has for economic and social organizations in the Latin American context. The importance of the conditions for the production units - goods and services -, both lucrative and non-profit, the structural problems that affect them, as well as the insertion of Latin American economies in the current globalization process is discussed. Fundamental elements of the management and management of organizations are addressed in relation to the strategy-environment relationship. Finally, considerations are made on core aspects of the concept of development, considering the performance of organizations in an integral and sustainable perspective. © 2019, Universidad del Zulia. All rights reserved.